Implementation of differentiated services in UMJaNetSim / Tan Geck Hiang - Tan , Geck Hiang (2004)
Deployment of a large number of Internet applications built around the Internet Protocol (IP), require a wide range of Quality of Service (QoS) in terms of throughput, delay and reliability (guarantee to reach the destination without any packet loss). Consequently, there is growing demand for replacing the current best-effort service paradigm with a model in which network traffic will be classified into different traffic classes based on their service needs and the classes will be treated differently. In this thesis, an existing object oriented and discrete event network simulator, UMJaNetSim is developed to enable the creation of a simulation environment for DiffServ framework. The goal of DiffServ is to define configurable types of packet forwarding that can provide service differentiation for large aggregates of network traffic. The DiffServ being implemented classifies packets into different PHB and proposes that packets with higher priority will receive relatively better service in any load condition in the network. This simulator intends to show that the proposed scheme improves the performance of existing schemes in terms of packet loss ratio, link utilization, end-to-end delay and throughput.